Corticotrophin‐releasing factor‐mediated effects of DA‐9701 in Postoperative Ileus Guinea Pig Model. Issue 10 (4th July 2018) - Jo, S. Y.; Hussain, Z.; Lee, Y. J.; Park, H.
Abstract: Background: Postoperative ileus (POI) is abdominal surgery‐induced impaired gastrointestinal (GI) motility. We aimed to investigate the effects of DA‐9701, a prokinetic agent formulated from Pharbitis Semen and Corydalis tuber, likely mediated via corticotrophin‐releasing factor (CRF) pathways, in a POI model. Methods: A laparotomy with cecal manipulation was performed to induce POI in guinea pigs. GI transit was measured based on charcoal migration after intragastric administration of DA‐9701 1, 3, and 10 mg kg −1 . CRF1 receptor antagonist, CP‐154 526 (subcutaneous) or agonist, human/rat (h/r) CRF (intraperitoneal) was injected. Then, plasma adrenocorticotropic hormone (ACTH) levels were measured, and the average intensity of the CRF expression was analyzed in the proximal colon and hypothalamus, and c‐Fos in the hypothalamus. Key Results: DA‐9701 significantly increased delayed GI transit in POI in a dose‐dependent manner and decreased plasma ACTH levels at 10 mg kg −1 . CP‐154 526 significantly decreased plasma ACTH levels but was not as effective on GI transit as DA‐9701 was. h/r CRF did not significantly affect GI transit and plasma ACTH levels. No significant difference was observed in GI transit and plasma ACTH levels in both groups administered DA‐9701 with h/r CRF and h/r CRF alone. CRF expression in the proximal colon decreased after DA‐9701 administration, but not significantly, compared with levels in POI alone. However, CRF expression in the hypothalamus was significantly lower in the DA‐9701‐pretreated POI than in the untreated POI. Conclusions and Inferences: The DA‐9701‐induced improvement in GI transit and inhibition of plasma ACTH levels was mediated by the central CRF pathway. Abstract : The DA‐9701‐induced improvement in GI transit and inhibition of plasma ACTH levels was mediated by the central CRF pathway.